Cytomorphology review of 100 newly diagnosed lower-risk MDS patients in the European LeukemiaNet MDS (EUMDS) registry reveals a high inter-observer concordance - de Swart, Louise; Smith, Alex; MacKenzie, Marius; Symeonidis, Argiris; Neukirchen, Judith; Mikulenková, Dana; Vallespí, Teresa; Zini, Gina; Paszkowska-Kowalewska, Malgorzata; Kruger, Anton; Saft, Leonie; Fenaux, Pierre; et al. (Annals of hematology, 2017)
The European LeukemiaNet MDS (EUMDS) registry is collecting data of myelodysplastic syndrome (MDS) patients belonging to the IPSS low or intermediate-1 category, newly diagnosed by local cytologists. The diagnosis of MDS can be challenging, and some data report inter-observer variability with regard to the assessment of the MDS subtype. In order to ensure that correct diagnoses were made by the participating centres, blood and bone marrow slides of 10% of the first 1000 patients were reviewed by an 11-person panel of cytomorphologists. All slides were rated by at least 3 panel members (median 8 panel members; range 3-9). Marrow slides from 98 out of 105 patients were of good quality and therefore could be rated properly according to the WHO 2001 classification, including assessment of dysplastic lineages. The agreement between the reviewers whether the diagnosis was MDS or non-MDS was strong with an intra-class correlation coefficient (ICC) of 0.85. Six cases were detected not to fit the entry criteria of the registry, because they were diagnosed uniformly as CMML or AML by the panel members. The agreement by WHO 2001 classification was strong as well (ICC = 0.83). The concordance of the assessment of dysplastic lineages was substantial for megakaryopoiesis and myelopoiesis and moderate for erythropoiesis. Our data show that in general, the inter-observer agreement was high and a very low percentage of misdiagnosed cases had been entered into the EUMDS registry. Further studies including histomorphology are warranted.
Keywords: Reproducibility of Results; Adult; senioři; senzitivita a specificita; Registries; Aged; Male; lidé; Cytodiagnosis; myelodysplastické syndromy; lidé středního věku; Humans; cytodiagnostika; Observer Variation; Diagnostics; odchylka pozorovatele; Middle Aged; reprodukovatelnost výsledků; Young Adult; Sensitivity and Specificity; senioři nad 80 let; registrace; vyšetřování kostní dřeně; Aged, 80 and over; Myelodysplastic Syndromes; mužské pohlaví; Myelodysplastic syndromes (MDS); Cytomorphology review; dospělí; Inter-observer variability; mladý dospělý; ženské pohlaví; Female; Bone Marrow Examination